Dealing with sexually transmitted infections in private pharmacies in Morocco - Nezha Nacer; Nadia Ouzennou; Samia Rkha (GarVal Editorial Ltda., 2023)
Context: Sexually transmitted infections continue to be a health problem in many countries. The management of these infections requires the mobilization of all health actors. Aims: To evaluate the management of sexually transmitted infections at private pharmacies in a Moroccan city. Methods: The simulated patient technique was used. Thirty-six pharmacies were visited to determine how cases of vaginal discharge syndrome and genital ulceration were managed in practice. Results: Rural (18) and urban (18) pharmacies were surveyed. The pharmacies visited were often of moderate (58.3%) to low (27.8%) activity and the activity of the pharmacy was significantly different (p=0.045) during the visit for vaginal discharge or genital ulceration. The duration of visits was less than five minutes in the majority of cases (91.7%). The nature of the syndrome vary significantly affected encounter duration (p=0.000). The proposition of medication to the simulated patient was carried out by 75% of the pharmacists/vendors (X = 3.36; σ = 0.860) and the type of syndrome very significantly affected the proposed management (p=0.009). The average prescription price was 298.32 dirhams per visit (σ = 39.353). None of the cases of genital ulceration or vaginal discharge were offered treatment that perfectly matched the protocol used by the Moroccan Ministry of Health. Conclusions: In the face of microbial resistance to antibiotics, sexually transmitted infections must be managed in the best conditions. In the future, studying the knowledge of these actors and proposing training on treatment protocols for sexually transmitted infections could contribute to the fight against these infections in this city.